(untitled) (Frontier in Medical and Health Research, 2026)
Background: Asthma is a chronic inflammatory airway illness that significantly reduces physical health and overall quality of life. One of the most commonly reported yet undertreated comorbidities in asthmatic patients is sleep disruption. Nocturnal symptoms—including cough, wheezing, chest tightness, and dyspnea—interfere with normal sleep architecture, leading to shorter sleep duration, longer sleep latency, frequent awakenings, and excessive daytime sleepiness. Despite global evidence linking asthma severity to poor sleep outcomes, data from South Asian clinical populations remain scarce. Objective: To evaluate sleep quality and its association with asthma severity in adult patients attending a tertiary hospital in Lahore, Pakistan. Methods: A cross-sectional study enrolled 180 asthma patients (age >14) via convenience sampling at Gulab Devi Teaching Hospital, Lahore. Asthma severity was categorized using GINA criteria; sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). Chi-square testing was used to analyze associations between PSQI sleep domains and asthma severity (SPSS v.26; significance at p<0.05). Results: Of 180 patients (60% male; mean age group 46–60 years), 96.7% showed clinically significant sleep disturbance: 30.6% had moderate poor sleep and 66.1% had severe poor sleep. All twelve chi-square correlations were statistically significant (p<0.05). Cough/wheeze (χ²=46.83, p<0.001) and daytime dysfunction (χ²=51.28, p<0.001) showed the highest correlations with asthma severity. A dose-response relationship was observed across all domains. Conclusion: Poor sleep quality is substantially and persistently correlated with asthma severity across all evaluated parameters. Systematic sleep assessment should be incorporated into standard asthma care in Pakistan.